An Analysis of English Loanword Used in Riau Pos Daily Newspaper - Estika Satriani (Universitas Lancang Kuning, 2018)
Most of Indonesian vocabularies now are derived from other languages such as from English. The phenomena caused by many new foreign words that used in Indonesia. It is called loanword. It means that a word from one language adapted into another language. This research was aimed to analyze and describe the types of English loanwords written in Riau Pos daily newspaper; simple word, complex word, and translated word. The research was descriptive design. The source of data in this research was article of Opini, Ekonomi-bisnis, and Politik that published on April 9th, 19th, 20th, 23rd 2016 in Riau Pos daily newpaper. The result of the research showed that there were 217 English loan word that used in Riau Pos daily newspaper. Complex word was the most frequently used which there were 122 of complex word, then there were 82 simple word used in Riau Pos daily newspaper, meanwhile translated word was the least frequently which there were 13 of translated word used in Riau pos daily newspaper. In conclusion it can contribute to linguistics fields and Indonesian language itself.